Epidemiology of Guillain-Barré syndrome in Finland 2004–2014 - Jussi O.T. Sipilä; Merja Soilu‐Hänninen; Jori O. Ruuskanen; Päivi Rautava; Ville Kytö (WILEY, 2022)
At total mean incidence of 0.84-1.1/100,000 the occurrence of Guillain-Barre syndrome (GBS) is reported to be low in Finland compared to other Caucasian populations. However, a recent study from Southwestern Finland reported an incidence of 1.82/100,000 which is comparable to other Caucasian populations. We analyzed discharge data covering the years 2004 through 2014 on all neurological admissions in all Finnish university and central hospitals with a primary diagnosis of GBS. A total of 989 admissions due to GBS (917 individuals) were identified. The standardized (European population) annual incidence rate was 1.70/100,000 person-years (95% confidence interval 1.60-1.81). GBS incidence had an increasing trend with age. The likelihood of GBS was higher among girls and adolescent women than boys and men of same age (male:female incidence rate ratio [IRR] 0.56), while in the older age groups (>19years) the occurrence of GBS was higher among males than females (male:female IRR 1.59). The incidence of GBS remained stable during the study period. There was no seasonal variation in GBS admission frequencies (p=0.28). No significant effect of the 2009-2010 H1N1 influenza or vaccination against it for GBS occurrence was observed. We suggest that GBS is as common, and has similar age-distribution in Finland as in other European countries. Sex-associated susceptibility for GBS appears to be different in children-adolescents and adults.